BBX28/BBX29, HY5 and BBX30/31 form a feedback loop to fine‐tune photomorphogenic development. (6th August 2020) - Song, Zhaoqing; Yan, Tingting; Liu, Jiujie; Bian, Yeting; Heng, Yueqin; Lin, Fang; Jiang, Yan; Wang Deng, Xing; Xu, Dongqing
SUMMARY: Light is one of the key environmental cues controlling photomorphogenic development in plants. A group of B‐box (BBX) proteins play critical roles in this developmental process through diverse regulatory mechanisms. In this study we report that BBX29 acts as a negative regulator of light signaling. BBX29 interacts with CONSTITUTIVELY PHOTOMORPHOGENIC 1 (COP1) and undergoes COP1‐mediated degradation in the dark. Mutant seedlings with loss of BBX29 function show shortened hypocotyls, while transgenic plants overexpressing BBX29 display elongated hypocotyls in the light. Both BBX28 and BBX29 interfere with the binding of ELONGATED HYPOCOTYL 5 (HY5) to the promoters of BBX30 and BBX31, consequently leading to the upregulation of their transcript levels. BBX30 and BBX31 associate with the promoter regions of BBX28 and BBX29, which in turn promotes the expression of these genes. Taken together, this study reveals a transcriptional feedback loop consisting of BBX28, BBX29, BBX30, BBX31, and HY5 that serves to fine‐tune photomorphogenesis in response to light in plants. Significance Statement: The B‐box (BBX) proteins are key regulators of light‐mediated development in plants, and they form complicated but delicate regulatory networks with other transcription factors in the regulation of these developmental processes. This study reveals that four BBX members, BBX28–BBX31, work in concert with ELONGATED HYPOCOTYL 5, which is a central regulator of light signaling, and together they form a transcriptional feedback loop that precisely controls photomorphogenic development in the light.